Edible Alliums – a source for crop diversification and nutritional security - Benke, Ashwini; Mahajan, Vijay; Gupta, A J; Singh, Major (Indian Horticulture, 2019)
Allium, a genus of monocotyledonous flowering plants includes nearly 750 different wild and cultivated species. Most of the Allium species, viz. Allium fistulosum, A. tuberosum, A. ampeloprasum, A. chinense and A. shoenoprasum are not much explored in India. These species have untapped reservoir of favourable genes as well as possesses ample potential in kind of flavour and nutrition which can be added in our diet. Exploiting such species will definitely enhance Indian edible Allium germplasm diversity as well as nutritional security of consumer. Cultivation of this species will give alternate source of income to farmers and foreign exchange to country as it has robust demand in international market.